2017
DOI: 10.2214/ajr.16.17418
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Renal Diffusion Tensor Imaging as a Correlate to Histopathology in Pediatric Renal Allografts

Abstract: FA is a noninvasive correlate of several important renal allograft histopathology scores and a potential noninvasive method of assessing renal allograft health in pediatric allograft recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…[68][69][70][71] In fibrotic kidneys, the diffuse interstitial fibrosis as well as tubular atrophy, cell infiltration, and glomerular scarring may also alter water diffusion and correlate well with renal FA in both animal models 72,73 and humans. 36,69,74,75…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
“…[68][69][70][71] In fibrotic kidneys, the diffuse interstitial fibrosis as well as tubular atrophy, cell infiltration, and glomerular scarring may also alter water diffusion and correlate well with renal FA in both animal models 72,73 and humans. 36,69,74,75…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
“…Li et al utilized the Kendall tau correlation coefficient and found that medullary FA values were inversely correlated with histopathology scores, such as tubulitis, interstitial inflammation, tubular atrophy, and interstitial fibrosis. Concomitantly, cortical FA values show an inverse correlation with peritubular capolaritis . Using a b value of 800 s/mm 2 , medullary FA values can even potentially determine whether pediatric renal allograft recipients need a change in their clinical management.…”
Section: Applications Of Renal Fmrimentioning
confidence: 99%
“…22 A recent study on pediatric renal allografts has shown a moderate correlation of medullary FA with several Banff histopathology scores (particularly at higher b-values) but not cortical FA. 34 Neither cortical nor medullary FA correlated with the glomerulitis (g) Banff score. This suggests that more specific biomarkers of renal microstructure are desirable.…”
Section: Introductionmentioning
confidence: 98%
“…However, FA remains unable to differentiate between different pathophysiological mechanisms underlying renal dysfunction . A recent study on pediatric renal allografts has shown a moderate correlation of medullary FA with several Banff histopathology scores (particularly at higher b‐values) but not cortical FA . Neither cortical nor medullary FA correlated with the glomerulitis (g) Banff score.…”
Section: Introductionmentioning
confidence: 99%